Exploring factors influencing Islamic financial literacy and its implications for the financial well-being of Muslim Youth in Malaysia. - Mohd Sumairi , Zikrilhafiz; Mohamed Shaarani , Ahmad Zakirullah; Habidin , Nurul Fadly (Journal of Islamic, Social, Economics and Development, 2025)
Islamic financial literacy provides significant effectiveness for individual financial well-being and for the stability of the economic community of Muslims. Nevertheless, some previous research has shown that the level of Islamic financial literacy among Muslim youth is still very low, thus causing difficulties for them in managing their finances. According to a report by Bank Negara Malaysia, youth bankruptcy rates have been on the rise, increasing 12% over the last five years, and the main contributors to this incapacity to pay include credit card debt and personal loans. Hence, this study was developed with four main objectives: (1) to assess the level of Islamic financial literacy among Muslim youth in the state of Selangor, (2) to identify the key factors contributing to low Islamic financial literacy and negative financial behaviours among Muslim youth, (3) to explore how Islamic financial literacy can influence and improve their financial well-being, and (4) to propose a conceptual framework (I-FINWELL Model) to enhance Islamic financial literacy and promote ethical financial practices aligned with Shariah principles. This qualitative study employed semi-structured interviews with five participants to better understand their experiences in managing financial challenges. The findings reveal that limited Islamic financial education in a formal and structured manner, insufficient guidance from family, and the dominance of conventional financial narratives on social media are the key variables affecting Islamic financial literacy among youth. Additionally, the prevalence of impulsive spending, over-reliance on debt, and lack of Shariah-compliant saving and investment habits were found to hinder their financial well-being. To address these issues, the study introduces the Integrative Model of Islamic Financial Literacy and Financial Well-Being of Muslim Youth (I-FINWELL) as a strategic framework that connects three dimensions: education, social and media influence, and financial behavioural development. Notably, this study contributes to the field by offering a comprehensive and practical conceptual model that bridges education, digital media, and ethical behaviour in the context of Islamic financial literacy. The I-FINWELL model can serve as a reference for governments, Islamic financial institutions, and academia in designing impactful strategies to enhance the financial literacy and long-term well-being of Muslim youth.